2023
DOI: 10.1002/fes3.437
|View full text |Cite
|
Sign up to set email alerts
|

A seven‐year study on the effects of four tillage modes on soil physicochemical properties, microbial biomass, enzymatic activities, and grain yield in a rice–ratoon rice cropping system

Abstract: Ratoon rice is resource efficient to produce economically sound and environmentally sustainable rice production. However, there is no more information on the relative impact of soil tillage practices on soil physical and chemical properties, microbial biomass, and enzymatic activity, and grain yield in a rice–ratoon rice cropping system remains to be tested. Systematic study of soil under ratooning rice model is a problem to be solved in the development of ratooning rice model. This study primarily investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 67 publications
1
0
0
Order By: Relevance
“…BG regulates the release of soil glucose, and UR regulates the decomposition of urea, both of which are important enzymes in soil C and N cycles [47,48]. We observed that tillage increased the activity of BG and UR, which was consistent with previous conclusions [49].…”
Section: Discussionsupporting
confidence: 90%
“…BG regulates the release of soil glucose, and UR regulates the decomposition of urea, both of which are important enzymes in soil C and N cycles [47,48]. We observed that tillage increased the activity of BG and UR, which was consistent with previous conclusions [49].…”
Section: Discussionsupporting
confidence: 90%